Research of infrastructure of investment and construction process - Kishchenko, T. (Ways to Improve Construction Efficiency, 2022)
The article considers the most important factors that led to the emergence of new activities that ensure the creation of high quality consumer value of construction projects, for financing, design, construction and management of which requires expert intervention. The study of investment and construction activities suggests that a group of professionals – functional participants – "promotes the investment process", and this, in turn, allows, according to the author, to distinguish them and combine them with the concept of infrastructure of investment and construction process. Much attention in the article is paid to the study of the essence of the concept of infrastructure as a set of institutions, organizations, government and commercial enterprises that ensure optimal functioning of the process, interaction and effective cooperation of its participants. In the context of the investment and construction process, as an independent subsystem, infrastructure is a set of organizational and legal forms that mediate the movement of the construction project to implementation, or a set of institutions, systems, enterprises serving the process and performing certain functions to ensure effective operation. The infrastructure of the investment and construction process is created by its functional participants, whose activities are commercial in nature and related to the organization of the investment process, increase investment efficiency, reduce costs of institutional investors, solve the problem of optimizing all resources. Therefore, the article considers and analyzes the development, consulting, engineering, auditing, acquiring activities, the emergence of which in the investment and construction process determined the demand for quality real estate, to finance, design, build and manage which requires expert intervention. It is noted that the emergence and development of infrastructure for investment and construction activities. focused on project management and implementation – ie coordination of all actions of the participants, reflects the process of intensive internal restructuring of the construction industry in order to improve economic conditions.